Chewing gum moderates the vigilance decrement. (12th March 2013) - Morgan, Kate; Johnson, Andrew J.; Miles, Christopher
<x xml:space="preserve">Abstract</x> We examine the impact of chewing gum on a Bakan‐type vigilance task that requires the continual updating of short‐term order memory. Forty participants completed a 30‐min auditory Bakan‐task either with, or without, the requirement to chew gum. Self‐rated measures of mood were taken both pre‐ and post‐task. As expected, the vigilance task produced a time‐dependent performance decrement indexed via decreases in target detections and lengthened correct reaction times (RTs), and a reduction in post‐task self‐rated alertness scores. The declines in both performance and subjective alertness were attenuated in the chewing‐gum group. In particular, correct RTs were significantly shorter following the chewing of gum in the latter stages of the task. Additionally, the gradients of decline for target detection and incline for correct RTs were both attenuated for the chewing‐gum group. These findings are consistent with the data of Tucha and Simpson (2011), Appetite, 56, 299–301, who showed beneficial effects of chewing gum in the latter stages of a 30 min visual attention task, and extend their data to a task that necessitates the continuous updating of order memory. It is noteworthy that our data contradict the claim (Kozlov, Hughes, & Jones, 2012, Q. J. Exp. Psychology, 65, 501–513) that chewing gum negatively impacts short‐term memory task performance.